Ossian and National Epic - Bär, Gerald (2014)
In the 18th century the appearance of the poems ascribed to Ossian triggered a great interest in national literatures and inspired the imagination and ultimately the productive reception of generations of (pre)romantic poets worldwide. Ossian was instrumental in the appreciation of folk poetry and instrumentalized in the creation of national literature. In the aftermath of Macpherson’s Ossianic publications several nation states as well as stateless nations rediscovered and glorified their own «barbaric» past with «national epics». This volume attempts to reconstitute partly the philological context in order to shed more light on Ossian and national epic in general, its development in European literature and its (re)emergence in different genres and other arts.